Let α = a + ib & β = x + iy

It is given that, β = 1

\( \sqrt{x^2+y^2}=1\)

\(x^2+y^2=1\)

\( | \dfrac{(x+iy)-(a+ib)}{1-(a-ib)(x+iy)}|\)

\( | \dfrac{(x-a)-i(y-b)}{1-(ax+aiy-ibx+by)}|\)

\( | \dfrac{(x-a)-i(y-b)}{(1-ax-by)+i(bx-ay)}|\)

\( \dfrac{\sqrt{(x-a)^2+(y-b)^2}}{\sqrt{(1-ax-by)^2(bx-ay)^2}}\)

Hence, proved

Answered by Pragya Singh | 1 year agoShow that 1 + i^{10} + i^{20} + i^{30} is a real number?

Solve the quadratic equations by factorization method only 6x^{2} – 17ix – 12 = 0

Solve the quadratic equations by factorization method only x^{2} + (1 – 2i)x – 2i = 0

Solve the quadratic equations by factorization method only x^{2} + 10ix – 21 = 0

Solve the quadratic equations by factorization method only 17x^{2} – 8x + 1 = 0